Bilimbi Fruit (Averrhoa bilimbi Linn.) Extract Protects Liver from Damage Induced by Reheated Palm Oil on Mice (Mus musculus) - Muhammad Hilmy Labibi; Suyatmi .; Zulaika Nur Afifah (Nexus Biomedika, 2016)
Introduction: Liver diseases such as hepatitis, cirrhosis hepatis, and fatty liver disease are serious health problem worldwide. Stress oxidative is involved in the pathogenesis of the diseases. Bilimbi fruit (Averrhoa bilimbi Linn.) contains flavonoid, triterpenoid saponin, vitamin A, and vitamin C which might protect the liver from stress oxidative. This research aimed to know the effect of Averrhoa bilimbi Linn. extract on the liver damage induced by reheated palm oil on mice. Methods: This was an experimental laboratory research with the post test only controlled group design. This research used 30 male Swiss webster mice aged 2-3 months and weighed 20 g weight divided randomly and equally into 5 groups. The normal control group (KKn) was given distilled water, the exposure group (KKp) was given reheated palm oil, and the 1st,2nd3rd treatment group (KP1, KP2, KP3) were given ethanolic extract of Averrhoa bilimbi Linn. in dose 5.6 mg, 11.2 mg, and 22.4 mg respectively. The induction for liver damage was done by giving reheated palm oil afterward. These treatments were given for 14 days. Mice were sacrificed on the 15th day by neck dislocation. The liver were obtained for preparation with paraffin block method and stained with HE. The Liver damage was assessed by quantifying of necrotic cells of each 100 cells in the centrolobular zone. Data was analyzed using One-Way ANOVA test and followed by Post Hoc test (?=0,05). Results: Mean of necrotic cells for KKn, KKp, KP1, KP2, and KP3 were 5.171.53; 78.084.74; 40.336.34; 30.176.29; and 19.005.89 cells respectively. One-Way ANOVA test showed a significant differences of liver damage score among five groups, *p=0.000. The results of Post Hoc test also showed significant difference between pairs of all group (*p =0.000). Conclusion: Averrhoa bilimbi Linn.extract protected liver from damage induced by reheated palm oil on mice. Keywords: Averrhoa bilimbi Linn. extract, reheated palm oil, liver histological damage